The ratio of systolic and diastolic pressure is associated with carotid and femoral atherosclerosis - Wang, Yuanping; Chen, Cheng; Lin, Qiaofen; Su, Qingling; Dai, Yiquan; Chen, Hongyu; He, Tianmin; Li, Xiantao; Feng, Ruimei; Huang, Wuqing; Hu, Zhijian; Chen, Jun; et al. (Frontiers in Cardiovascular Medicine, 2024)
Although the impact of hypertension on carotid intima-media thickness (IMT) and plaques has been well established, its association with femoral IMT and plaques has not been extensively examined. In addition, the role of the ratio of systolic and diastolic pressure (SDR) in the subclinical atherosclerosis (AS) risk remains unknown. We assessed the relationship between SDR and carotid and femoral AS in a general population.A total of 7263 participants aged 35-74 years enrolled from January 2019 to June 2021 in a southeast region of China were included in a cross-sectional study. Systolic and diastolic blood pressure (SBP and DBP) were used to define SDR. Ultrasonography was applied to assess the AS, including thickened IMT (TIMT) and plaque in carotid and femoral arteries.Logistic regression and restricted cubic spline (RCS) models were the main approaches.The prevalence of TIMT, plaque, and AS were 17.3%, 12.4%, and 22.7% in the carotid artery; 15.2%, 10.7%, and 19.5% in femoral artery; and 23.8%, 17.9% and 30.0% in either carotid or femoral artery, respectively. Multivariable logistic regression analysis found significant positive association between high-tertile SDR and the higher risk of overall TIMT (OR=1.28, 95% CI=1.10-1.49), plaques (OR=1.36, 95%CI=1.16-1.61), or AS (OR=1.36, 95% CI=1.17-1.57), especially in carotid artery. RCS analysis further revealed the observed positive associations were linear. Further analyses showed that as compared to the low-tertile SDR and non-hypertension group, high-tertile SDR was associated with increased risks of overall and carotid TIMT, plaques, or AS in both groups with or without hypertension.SDR is related to a higher risk of subclinical AS, regardless of hypertension or not, suggesting that as a readily obtainable index, SDR can contribute to provide additional predictive value for AS.